Messages from the Malaysian Diabetes Registries on Diabetes Care in Malaysian public healthcare facilities. Issue 5 (October 2016) - Chew, Boon-How; Lee, Ping-Yein; Cheong, Ai-Theng; Ismail, Mastura; Shariff-Ghazali, Sazlina; Goh, Pik-Pin
Abstract: A persistent and increasing prevalence of diagnosed and undiagnosed diabetes mellitus has recently been reported in the National Health and Morbidity Survey 2015. This commentary recapitulates the relevant and valuable lessons in the Malaysian national diabetes registries to inform the healthcare stakeholders and policy makers on potential areas of clinical practice improvement and future researches. Under performance of the process measures and sub-optimal control of HbA1c, blood pressure and lipids profile were prevalent (<40% achieved treatment targets). Although these had improved slightly from 2009 to 2012, diabetes co-morbidities (hypertension and dyslipidaemia) and complications had also increased. Prevalence of insulin use had doubled, and lipid lowering agent use had increased about 50% in 2012 compared to 2009. We identified six clinical areas for urgent attention and improvement, and three potential areas for future research.